Celiac disease unmasked by acute severe iron deficiency anemia - Marcelle G. Meseeha; Maximos N. Attia; Victor O. Kolade (Greater Baltimore Medical Center, 2016)
The prevalence of celiac disease (CD) appears to be increasing in the United States. However, the proportion of new CD cases with atypical presentations is also rising. We present the case of a 49-year-old woman who was diagnosed with CD in the setting of new, severe iron-deficiency anemia, 13 years into treatment of diarrhea-predominant irritable bowel syndrome associated with chronic mildly elevated liver function tests. While CD and iron deficiency anemia are common, this is a rare presentation of CD.